PENGARUH TERAPI KOMPRES JAHE TERHADAP TINGKAT NYERI OSTEOARTRITIS PADA LANSIA DI UPT. PUSKESMAS GULUK-GULUK - Syaifurrahman Hidayat; Ivan Dwi Arya Putra (Wiraraja Medika : Jurnal Kesehatan, 2016)
Osteoarthritis is a degenerative joint disease that is caused by many factors, among others; allergic reactions, infections, genetics, and because of the aging process of a person. The disease that is often experienced by the elderly is a joint disease or osteoarthritis. Osteoarthritis ranks first chronic diseases suffered by older people (44%), followed by hypertension (39%), reduced hearing or deafness (28%) and heart disease (27%). This is common in the joints of the body weight retention (knee and hip), the joints in the fingers and spine. This study aimed to identify the effect of ginger compress to decrease the level of pain in osteoarthritis patients at health center UPT Guluk-guluk.This research is pre-experiment is one group prepost test design, with sampling purposive technique. The population in this study were 58 people with a total sample of 41 people. Data analysis in this study using the Wilcoxon test.The results of this study previously conducted before the pain level in patients given ginger compress majority of respondents experienced a level of moderate pain (73.2%) and the level of pain in patients after given a ginger compress majority of respondents experienced a level of moderate pain (58.5%). Analysis test the effect of ginger compress to decrease the level of pain in osteoarthritis patients was measured using the Wilcoxon test showed p = 0.000 (<0.05).The conclusions of this study showed that there is an effect of ginger compress on the level of pain in osteoarthritis patients at health center UPT Guluk -guluk. It is advisable in future studies in order to conduct research using other variables that influence the reduction of pain in osteoarthritis patients.